2016
DOI: 10.1002/stem.2509
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cell Secretion of Programmed Death-1 Ligands Regulates T Cell Mediated Immunosuppression

Abstract: Mesenchymal stromal cells (MSCs) exert broad immunosuppressive potential, modulating the activity of cells of innate and adaptive immune systems. As MSCs become accepted as a therapeutic option for the treatment of immunological disorders such as Graft versus Host Disease, our need to understand the intricate details by which they exert their effects is crucial. Programmed death‐1 (PD‐1) is an important regulator in T cell activation and homeostatic control. It has been reported that this pathway may be import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
257
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(286 citation statements)
references
References 51 publications
14
257
0
3
Order By: Relevance
“…IFNγ and TNF-α are the most important T cell effector cytokines in MSC immunomodulatory effects. Davies et al [18] demonstrated that MSCs express and secrete programmed death ligands (PD-L) 1 and 2. They reported PD-L1- and PD-L2-mediated suppression of T cell proliferation by MSCs, IL-2 secretion, and induction of an irreversible hyporesponsive state, as well as apoptosis.…”
Section: Biological Properties Of Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…IFNγ and TNF-α are the most important T cell effector cytokines in MSC immunomodulatory effects. Davies et al [18] demonstrated that MSCs express and secrete programmed death ligands (PD-L) 1 and 2. They reported PD-L1- and PD-L2-mediated suppression of T cell proliferation by MSCs, IL-2 secretion, and induction of an irreversible hyporesponsive state, as well as apoptosis.…”
Section: Biological Properties Of Mscsmentioning
confidence: 99%
“…In vitro models indicate that MSCs induce regulatory T cells and also sustain their survival and suppressive phenotypes [19]. It is documented that MSCs affect the status of T cells and skew them towards a regulatory phenotype [18]. MSCs also interact with B cells by inhibiting B cell responses [19] which results in cell cycle arrest, decreased immunoglobulin production, and impaired chemotaxis.…”
Section: Biological Properties Of Mscsmentioning
confidence: 99%
“…CAFs have been shown to be suppressive, and using in vitro assays, some of these subsets like MSCs have been shown to exhibit direct immunosuppressive activities in a manner similar to regulatory T cells (T reg )[11,12]. CAFs can impair CTL activation, cytokine production, and cytotoxicity through the production of soluble factors such as IL10, TGF-β, or VEGF, as well as through metabolic reprograming via prostaglandin E2 (PGE2), indoleamine 2,3-dioxygenase (IDO), and arginase[2,13] or expression of T cell checkpoint molecules like programmed death-ligand 1 (PD-L1)[2,13].…”
Section: Cafs As Regulators Of T Cell Functionmentioning
confidence: 99%
“…Although a blockade of PD‐L1 did not alter the overall T cell proliferative responses, it resulted in a reduced L‐MSC–induced inhibition in 6 of the 11 experiments (Fig. B), suggesting that this mechanism may play a partial role in the anti–T cell proliferative responses, likely through soluble factors . Second, PTGS1 was found to be one of most abundant RNA sequences in L‐MSCs (top 1% of all detected transcripts) and was detected at significantly higher amounts in L‐MSCs versus A‐MSCs and BM‐MSCs.…”
Section: Discussionmentioning
confidence: 93%